Priorities and Strategies for Education : A world Bank Review - World Bank, Washington, DC.; World Bank, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1995)
This book examines what countries and international organizations can do to meet the great educational challenges they face. Higher living standards, better health, increased productivity, improved well-being for women and their families, and good government all depend on widespread education. The book is divided into three parts with 12 chapters. A primary conclusion is that the top priority for most countries is to ensure universal, high-quality basic education, with special attention to schooling for girls. Other important issues discussed include: (1) the conditions for effective learning; (2) the compatibility of private and public provision and financing of education; and (3) the need for community and parental involvement and local autonomy in running schools. Special sections are devoted to education and reform in former centrally planned economies. The book closes with a survey of the World Bank's support for education projects and reforms in developing countries. Contains 274 references. (EH)
Availability: The World Bank, 1818 H Street, N.W., Washington, DC 20433.
Microfiche.
Keywords: Educational Planning